Consumer Exposure to Antimicrobial Resistant Bacteria From Food at Swiss Retail Level - Jans, Christoph; Sarno, Eleonora; Collineau, Lucie; Meile, Leo; Stärk, Katharina D. C.; Stephan, Roger (Frontiers in Microbiology, 2018)
Background Antimicrobial resistance (AMR) in bacteria is an increasing health concern. The spread of AMR bacteria (AMRB) between animals and humans via the food chain and the exchange of AMR genes requires holistic approaches for risk mitigation. The AMRB exposure of humans via food is currently only poorly understood leaving an important gap for intervention design. Method This study aimed to assess AMRB prevalence in retail food and subsequent exposure of Swiss consumers in a systematic literature review of data published between 1996 and 2016 covering the Swiss agriculture sector and relevant imported food. Results Data from 313 out of 9’473 collected studies were extracted yielding 122’438 food samples and 38’362 bacteria isolates of which 30’092 samples and 8’799 isolates were AMR positive. A median AMRB prevalence of >50% was observed for meat and seafood harboring Campylobacter, Enterococcus, Salmonella, E. coli, Listeria and Vibrio spp. and to a lesser prevalence for milk products harboring starter culture bacteria. Gram-negative AMRB featured predominantly AMR against aminoglycosides, cephalosporins, fluoroquinolones, penicillins, sulfonamides and tetracyclines observed at AMR exposures scores of levels 1 (medium) and 2 (high) for Campylobacter, Salmonella, E. coli in meat as well as Vibrio and E. coli in seafood. Gram-positive AMRB featured AMR against glycoproteins, lincosamides, macrolides and nitrofurans for Staphylococcus and Enterococcus in meat sources, Staphylococcus in seafood as well as Enterococcus and technologically important bacteria (incl. starters) in fermented or processed dairy products. Knowledge gaps were identified for AMR prevalence in dairy, plant, fermented meat and novel food products and for the role of specific indicator bacteria (Staphylococcus, Enterococcus), starter culture bacteria and their mobile genetic elements in AMR gene transfer. Conclusion Raw meat, milk, seafood and certain fermented dairy products featured a medium to high potential of AMR exposure for Gram-negative and Gram-positive foodborne pathogens and indicator bacteria. Food at retail, additional food categories including fermented and novel foods as well as technologically important bacteria and AMR genetics are recommended to be better integrated into systematic One Health AMR surveillance and mitigation strategies to close observed knowledge gaps and enable a comprehensive AMR risk assessment for consumers.